1998
DOI: 10.1016/s0014-5793(97)01616-5
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Bcl‐XL prevents caspase‐3‐mediated activation of DNA fragmentation factor (DFF) produced by treatment with the photochemotherapeutic agent BPD‐MA

Abstract: Photodynamic therapy (PDT) is a clinically effective cancer treatment. For human promyelocytic leukemia HL-60 cells, cleavage of pro-caspase-3 (CPP32/Yama/apopain) into its proteolytically active subunits rapidly follows the photodynamic treatment of these cells with cytotoxic levels of the photosensitizer benzoporphyrin derivative monoacid ring A and visible light. Cleavage of a recently identified cytosolic 45 kDa protein, DNA fragmentation factor (DFF), is required for endonuclease activation leading to DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 22 publications
(51 reference statements)
1
16
0
Order By: Relevance
“…In this case, Bcl-2 overexpression prevented pro-caspase-3 and -6 cleavage, proteolysis of PARP and formation of hypodiploid DNA [77]. Overexpression of Bcl-x L in HL-60 cells also prevented PDT-induced cleavage of pro-caspase-3 and DNA fragmentation [76]. Enforced expression of Bcl-2 also delayed PDT-induced apoptotic death in a rat/mouse T cell hybridoma (PC60R1R2) sensitized with hypericin, by delaying cytochrome C release, pro-caspase-3 activation and PARP cleavage [68], and similar findings were reported in Jurkat cells photosensitized with hypericin [69].…”
Section: Role Of the Bcl-2 Family Of Proteins In Pdtmentioning
confidence: 86%
See 1 more Smart Citation
“…In this case, Bcl-2 overexpression prevented pro-caspase-3 and -6 cleavage, proteolysis of PARP and formation of hypodiploid DNA [77]. Overexpression of Bcl-x L in HL-60 cells also prevented PDT-induced cleavage of pro-caspase-3 and DNA fragmentation [76]. Enforced expression of Bcl-2 also delayed PDT-induced apoptotic death in a rat/mouse T cell hybridoma (PC60R1R2) sensitized with hypericin, by delaying cytochrome C release, pro-caspase-3 activation and PARP cleavage [68], and similar findings were reported in Jurkat cells photosensitized with hypericin [69].…”
Section: Role Of the Bcl-2 Family Of Proteins In Pdtmentioning
confidence: 86%
“…Also, expression of CrmA did not affect the kinetics of cytochrome C release Jurkat human lymphoma T cells [295] and procaspase-3 cleavage in a rat/mouse T cell hybridoma sensitized with hypericin [68], suggesting that caspase-8 does not play a major role in the demise process in this model. The activation of caspases in photosensitized cells leads to the cleavage of a number of other cell proteins, including Bap-31 (shuttle protein between the ER and the intermediate compartment and/or Golgi complex [71]), DNA-dependent protein kinase (catalytic subunit) (DNA-PK CS [75]), ICAD (inhibitor of caspase activated DNAse); prevents DNA fragmentation via binding to caspase-activated deoxyribonuclease [76]), focal adhesion kinase (FAK, a kinase involved in the regulation of cell adhesion [73]), lamins (structural components of the nuclear envelope [73]), PARP (poly(ADP-ribose) polymerase, a DNA repair enzyme [18,20,44,54,68,71,72,75,[77][78][79][80][81][82][83][84][85]) and Ras GTPase-activating protein (Ras-GAP, a negative regulator of the Ras signaling pathway [71]). DNA fragmentation in segments that are multiples of 180 -200 bp, another hallmark of apoptotic cell death [86], was also observed in PDT, using different cell types and sensitizers (Table 1).…”
Section: Role Of Caspases In Pdtmentioning
confidence: 99%
“…19 Briefly, fluorometric caspase-3 protease activity assays were performed in 96-well plates by incubating 50 L of cell lysate (10 g) with 100 L of reaction buffer (1% NP-40, 20 mmol/L Tris, pH 7.5, 137 mmol/L NaCl, 10% glycerol) and 100 mol/L of peptidic substrate Ac-DEVD-AMC (Calbiochem) at 37°C for 2 hours. The rate of caspase enzymatic hydrolysis was measured by release of AMC from the caspase substrate (emission of 460 nm on excitation at 380 nm).…”
Section: Caspase-3 Protease Activity Assaysmentioning
confidence: 99%
“…The rate of caspase enzymatic hydrolysis was measured by release of AMC from the caspase substrate (emission of 460 nm on excitation at 380 nm). 19 PARP cleavage analysis was performed by immunoblotting with PARP (Santa Cruz Biotechnology Inc). After incubation with horseradish peroxidase-labeled anti-goat-IgG antibody (1:5000) and detection with an enhanced chemiluminescence detection system (Amersham), bands were visualized by autoradiography.…”
Section: Caspase-3 Protease Activity Assaysmentioning
confidence: 99%
“…This endonuclease, CAD/CPAN, is only activated during apoptosis and is, therefore, believed to be responsible for DNA fragmentation (Halenbeck et al, 1998;Sakahira et al, 1998). We have shown that caspase-3-dependent cleavage of DFF occurs in PDTtreated HL-60 (Granville et al, 1998b) and HeLa cells (Carthy et al, 1998).…”
mentioning
confidence: 99%